Building Quality Culture of Higher Education by Implementation of Internal Quality Assurance System (An Empirical Evidence) - Anik Herminingsih; Rizka Donny Agung Saputra (Eduvest - Journal of Universal Studies, 2025)
Since 1998, the Indonesian government's regulations on higher education institutions have moved towards granting autonomy, which includes accreditation based on the Internal Quality Assurance System (IQAS). The goal is for the introduction of SPMI to lead to a culture of excellent quality in higher education. This research seeks to bridge the gap in empirical studies connecting the adoption of IQAS with its impact on the cultivation of a culture of quality in higher education. The research employs quantitative techniques to gather data through a survey utilizing a Likert Internascale. Data was evaluated utilizing structural equation modeling and handled through the AMOS software. The findings indicated that integrating IQAS had a beneficial and noteworthy impact on quality culture in a higher education establishment.